Multiple Intelligences-based Interactive Multimedia to Improve Students’ Multiple Intelligences in Kindergarten - Astiti, Putu Juli; Parwati, Ni Nyoman; Tegeh, I Made; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2024)
The main problem in this research is that students' multiple intelligences have not been developed according to their respective talents and interests. This research aims to develop multiple intelligence-oriented multimedia, to increase the multiple intelligences of students in kindergarten. The research method used is development using the ADDIE model. The instruments used were questionnaires and observation sheets. Questionnaires are used to measure the validity and practicality of multimedia by experts and users. Observation sheets are used to measure the effectiveness of multimedia in increasing the multiple intelligences of students in kindergarten. The questionnaire was analyzed quantitatively and descriptively, and the observation sheet was analyzed using quantitative and qualitative descriptive analysis methods. The research results showed that the validity of the design aspect was 93.53%, the learning media aspect was 90.00%, and the learning content aspect was 95.00%. The practicality of interactive multimedia through individual testing obtained a percentage level of 96.67%, and small groups obtained a percentage level of 96.67%. The effectiveness test shows that interactive multimedia is able to develop students' intelligence specifically in five aspects, namely logical-mathematical, musical, kinaesthetic, visual-spatial, and verbal linguistics.